1983
DOI: 10.1139/v83-304
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectral study of amino-acid complexes of Nd(III)

Abstract: Neodymium(III) complexes with histidine and diols (ethancdiol, prop-1,2-diol. but-2,3-diol, 2-butene-1,4-cliol, pent-1,5-diol, and hex-1,6-diol) of the type MAB, MA2B, and MAB2 have been synthesized and characterised. The values of Slater–Condon (Fk), Lande (ζ4f) spin orbital interactions, oscillator strength (P). and Judd–Ofelt (Tλ) intensity parameters have been calculated. Using these parameters, energies and intensities often levels in all the complexes in the region 360–920 nm have been computed. The agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Lanthanide elements have extensive application in industries, agriculture, and biomolecular reactions, so it has become very important to understand the behaviour of trivalent lanthanide ions in biological system [1,2]. The co-ordination chemistry of lanthanide in solution state has become more important with the increase use of lanthanides as probes in the exploration of the structural function of biomolecular reactions [3][4][5][6] specially due to its ability to replace Ca(II) in a specific manner [7][8][9][10]. In our previous study [11], we have reported the interaction of Pr(III) with amino acids in aqueous and different aquated organic solvents by using 4f-4f absorption spectra as probes and thereby calculating energy interaction parameters like Slater-Condon (F K ) factor, Racah (E k ), Lande factor (ξ 4f ), nephelauxetic ratio (β), bonding (b 1/2 ), percentage covalency (δ), and parameters like calculated values of oscillator strength (P) and computed values of electric dipole intensity parameters, T λ (λ = 2, 4, 6).…”
Section: Introductionmentioning
confidence: 99%
“…Lanthanide elements have extensive application in industries, agriculture, and biomolecular reactions, so it has become very important to understand the behaviour of trivalent lanthanide ions in biological system [1,2]. The co-ordination chemistry of lanthanide in solution state has become more important with the increase use of lanthanides as probes in the exploration of the structural function of biomolecular reactions [3][4][5][6] specially due to its ability to replace Ca(II) in a specific manner [7][8][9][10]. In our previous study [11], we have reported the interaction of Pr(III) with amino acids in aqueous and different aquated organic solvents by using 4f-4f absorption spectra as probes and thereby calculating energy interaction parameters like Slater-Condon (F K ) factor, Racah (E k ), Lande factor (ξ 4f ), nephelauxetic ratio (β), bonding (b 1/2 ), percentage covalency (δ), and parameters like calculated values of oscillator strength (P) and computed values of electric dipole intensity parameters, T λ (λ = 2, 4, 6).…”
Section: Introductionmentioning
confidence: 99%